Assessment of the allergenicity and antigenicity potential of enzymatically hydrolyzed cow milk. (February 2022) - Liang, Xiaona; Yang, Hui; Luo, Xue; Chen, Na; Ai, Zhisong; Xing, Yu; Huang, Wei; Wang, Zongzhou; Zheng, Yan; Yue, Xiqing
Abstract: Cow milk allergy is a major cause of food hypersensitivity in infants and children. However, to the best of our knowledge, there has been minimal research on the antigenicity of cow milk (CM). As it is currently unknown if enzymatically hydrolyzed cow milk (HM) induces severe immunogenic responses, the potential allergenicity of HM was systematically evaluated in this work. HM effectively attenuated symptoms of weight loss and diarrhea, suppressed levels of mast cell tryptase, and relieved allergic inflammation of the intestine. Moreover, HM reduced the B220 + cell count in mouse blood. In addition, in vitro studies demonstrated that gastrointestinal digestion of HM was not resistant to pepsin or trypsin. Thus, HM effectively alleviated allergic reactions and exhibited lower potential allergenicity. These results provide practical information for the future development of hypoallergenic CM products. Highlights: Assessment of the allergenicity potential in HM. HM could effectively attenuate symptoms of weight loss and diarrhea. HM could suppress MCT levels, relieve allergic inflammation of intestines. HM could reduce B220 + cell count in the blood of mice. HM was not resistant to pepsin or trypsin in vitro digestion.